2023
DOI: 10.1038/s41598-023-29108-8
|View full text |Cite
|
Sign up to set email alerts
|

Rare variant aggregation in 148,508 exomes identifies genes associated with proxy dementia

Abstract: Proxy phenotypes allow for the utilization of genetic data from large population cohorts to analyze late-onset diseases by using parental diagnoses as a proxy for genetic disease risk. Proxy phenotypes based on parental diagnosis status have been used in previous studies to identify common variants associated with Alzheimer’s disease. As of yet, proxy phenotypes have not been used to identify genes associated with Alzheimer’s disease through rare variants. Here we show that a proxy Alzheimer’s disease/dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Similar gene-based analysis studies were conducted in EA samples. One large genome-wide gene-based AD study conducted in the UK BioBank on different categories of rare missense/LoF variants found that three gene regions were associated with AD parent proxy cases, including TOMM40/APOE [55]. Notably, detection of these regions depended on resolving variants into categories of high confidence and predicted loss-of-function effects.…”
Section: Discussionmentioning
confidence: 99%
“…Similar gene-based analysis studies were conducted in EA samples. One large genome-wide gene-based AD study conducted in the UK BioBank on different categories of rare missense/LoF variants found that three gene regions were associated with AD parent proxy cases, including TOMM40/APOE [55]. Notably, detection of these regions depended on resolving variants into categories of high confidence and predicted loss-of-function effects.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increased microglia activations and inflammasome formations were found in patients with TOMM40 F113L or F131L [9]. Even though TOMM40 Arg239Trp was a rare variant in a conserved region of TOMM40, its association with AD or any forms of neurodegeneration remained unclear [59].…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis in 2019 found a significant enrichment of PTC and missense mutations in patients with an OR of 2.6 and 1.8, respectively, 38 while a gene‐burden test in exome sequencing data of 32,558 Caucasian individuals suggested significant ORs of 1.7 and 1.4 63 . A similar approach on 148,508 individuals, of whom 22,080 had at least one parent with AD/dementia or AD diagnosis themselves, found a nominally significant enrichment of rare ABCA7 variants in disease, although an OR was not reported 64 . Power in this cohort to find significance may have been decreased by the proxy approach in which not all 22,080 AD‐classified individuals actually developed AD, carried risk variants or may have had parents with other types of dementia.…”
Section: Abca7 Ad‐associated Variantsmentioning
confidence: 97%